SUMMER STORMS, FOOD, AND REPRESENTATIONS OF THE CLIMATE CRISIS IN BRIT BILDØEN’S "SJU DAGAR I AUGUST" AND AGNAR LIRHUS’S "LITEN KOKEBOK" - BOZÎNTAN, Georgiana (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Summer Storms, Food, and Representations of the Climate Crisis in Brit Bildøen’s Sju dagar i august and Agnar Lirhus’s Liten kokebok. This article discusses representations of climate change in contemporary realistic fiction from Norway. I first focus my attention on the depiction of extreme weather and “risk society” in Brit Bildøen’s Sju dagar i august (Seven days in august, 2014) and then explore the concept of “ecological masculinities” and expressions of care in Agnar Lirhus’s Liten kokebok (Little cookbook, 2016). Although the two novels I discuss thematise climatic disruptions in different ways, they are similarly intertwining characters’ experiences of the natural world with personal feelings of loss and grief. I thus suggest that climate change imagery in Norwegian realistic fiction is often interwoven with an affective dimension. Finally, the aim of this article is to illustrate how the climate crisis has pervaded Norwegian literature, while providing some examples of how texts that lay outside of what is typically considered the cli-fi novel have the potential to engage with this theme. Furtuni de Vară, Mâncare și Reprezentări ale Crizei Climatice în Sju dagar i august de Brit Bildøen și Liten kokebok de Agnar Lirhus. Acest articol discută reprezentări ale schimbărilor climatice în ficțiunea realistă contemporană din Norvegia. Îmi îndrept atenția mai întâi asupra portretizării fenomenelor meteorologice extreme și a „societății riscului” în romanul Sju dagar i august (Șapte zile din august, 2014) de Brit Bildøen, iar apoi examinez conceptul de „masculinități ecologice” și formele de manifestare a grijii în romanul Liten kokebok (Mica cartea de bucate, 2016) de Agnar Lirhus. Deși cele două romane discutate tematizează perturbările climatice în moduri diferite, ele sunt similare prin felul în care experiența lumii naturale e asociată cu sentimentele de doliu și durere cu care se confruntă personajele. În felul acesta, sugerez că imaginarul schimbărilor climatice în ficțiunea realistă norvegiană se împletește cu o dimensiune afectivă. În final, scopul acestui articol este de a ilustra cum tematica crizei climatice a pătruns în literatura norvegiană, oferind exemple care arată cum texte care nu sunt considerate în mod tipic ca aparținând genului cli-fi au potențialul de a aborda această tematică. Cuvinte-cheie: narațiuni despre schimbări climatice, ficțiune norvegiană contemporană, societatea riscului, fenomene meteorologice extreme, masculinități ecologice, grijă, Brit Bildøen, Agnar Lirhus Article history: Received 10 February 2023; Revised 3 May 2023; Accepted 30 May 2023; Available online 23 June 2023; Available print 30 June 2023.